2014
DOI: 10.1159/000360754
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Spot Sign on Computed Tomography Angiography as a Predictor of Haematoma Enlargement after Acute Spontaneous Intracerebral Haemorrhage: A Systematic Review

Abstract: Background: A common early complication of intracerebral haemorrhage (ICH) is haematoma enlargement (HE), a strong independent predictor of a poor outcome. Therapeutic options to limit haematoma progression are currently scarce. Haemostatic therapy may be effective in patients with ICH, but it carries the risk of thromboembolic events in unselected patients. Accurate patient selection would, therefore, be of key importance for delivering potentially successful therapeutic strategies. Currently, there is no gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Then we identified 47 relevant original studies after removal of duplications. Twenty-eight studies were further excluded, involving 5 studies of secondary ICH [22] [26] , 3 case reports [27] [29] , 2 review article [10] , [11] , 15 studies with insufficiently detailed records of HE data [7] , [30] [44] , and 3 studies with definition of HE contradicting with our HE criteria [45] [47] . Then we carefully assessed studies carried out by the same institutions [9] , [48] [53] , and data from two identical cohorts were incorporated together [48] , [49] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we identified 47 relevant original studies after removal of duplications. Twenty-eight studies were further excluded, involving 5 studies of secondary ICH [22] [26] , 3 case reports [27] [29] , 2 review article [10] , [11] , 15 studies with insufficiently detailed records of HE data [7] , [30] [44] , and 3 studies with definition of HE contradicting with our HE criteria [45] [47] . Then we carefully assessed studies carried out by the same institutions [9] , [48] [53] , and data from two identical cohorts were incorporated together [48] , [49] .…”
Section: Resultsmentioning
confidence: 99%
“…Original studies on spot sign differed in population, imaging techniques, radiographic criteria, and definition of outcomes, with a wide range of predictive values. Two recent reviews have summarized the role of CTA spot sign in primary ICH [10] , [11] . However, no published report has explored the predictive accuracy of spot sign by using a meta-analytic approach.…”
Section: Introductionmentioning
confidence: 99%
“…We did not evaluate cortical brain microbleeds, which might serve as a predictor of ischemic brain lesions and may also represent an imaging marker of active vasculopathy [29] , or other potential prognostic values of neuroradiological biomarkers seen in susceptibility weighted imaging sequences in MRI. In a recent review, studies of the spot sign appeared diverse and therefore complex to interpret due to heterogeneity and potential of bias in the selected studies [30] . However, Havsteen et al [31] found an association between the absence or presence of a spot sign and long-term mortality and functional outcome in sICH patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another parameter predicting increasing hematoma size is the well-established spot sign (SS) visible in computed tomographic angiography (CTA). 7,8 The major advantage of the BS is the visibility in NCCT which offers a greater availability in clinical routine and a much faster and cheaper assessment. In addition, allergic reactions to contrast medium and renal dysfunction present possible contraindications for contrast application.…”
mentioning
confidence: 99%